2010
DOI: 10.1159/000321110
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral Administration of <i>Lactobacillus acidophilus</i> L-92 on the Symptoms and Serum Markers of Atopic Dermatitis in Children

Abstract: Background: Few studies have investigated the complementary effects of long-term oral administration of Lactobacillus acidophilus on traditional medical therapy in the treatment of patients with atopic dermatitis (AD). Methods: The Atopic Dermatitis Area and Severity Index was used to evaluate AD severity. Symptom severity was assessed using the symptom score. The effect of medical therapy was evaluated by adding the medication score, calculated as the sum of each product of the amount of steroid ointment used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 66 publications
2
47
0
2
Order By: Relevance
“…Sixteen [289][290][291][292][293][294][295][296][297][298][299][300][301][302][303][304] new trials were reported after 2000. Nearly all of the 16 trials reported compared a probiotic against an inactive placebo or occasionally against no treatment.…”
Section: Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixteen [289][290][291][292][293][294][295][296][297][298][299][300][301][302][303][304] new trials were reported after 2000. Nearly all of the 16 trials reported compared a probiotic against an inactive placebo or occasionally against no treatment.…”
Section: Studiesmentioning
confidence: 99%
“…Only one trial compared two strains of probiotics in hydrolysed milk formula against each other and a placebo of maltodextrin in a three-arm comparison trial. 302 In 13 [289][290][291][292][293][295][296][297][298]300,302 of the 16 trials the participants were children, particularly infants. Only three trials, 294,299,301 conducted in Japan and Italy, included adult participants.…”
Section: Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects can be related to the probiotic effects on the hosts' immunological functions such as improvement of the barrier function and increasing allergen-specific IgA levels, which are essential for the development of tolerance and can be considered as a marker for immune maturation (113,134,135,(137)(138)(139) . Furthermore, probiotics have been suggested to have immunomodulatory impacts that affect the Th1/Th2 balance such as stimulation of Th1-type immune responses, induction of apoptosis of Th2 cells and induction of regulatory T and dendritic cells (16,138,(140)(141)(142)(143)(144) .…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
“…They observed that the probiotic had potential to improve symptoms in atopic dermatitis 46 . Han et al 47 showed effect on treatment of atopic dermatitis in children (18 moths-13 years old) when used 0.5x10 10 …”
mentioning
confidence: 99%